Three-dimensional nitrogen-doped dual carbon network anode enabling high-performance sodium-ion hybrid capacitors. (10th February 2022) - Qiu, Daping; Yue, Cheng; Qiu, Chuang; Xian, Liying; Li, Min; Wang, Feng; Yang, Ru
Highlights: A three-dimensional dumpling-like glyururil-derived porous carbon@RGO composite was successfully synthesized. The composite delivers mesopores-macropores hierarchical porous network and high nitrogen-doping level (10.29 at.%). A sodium-ion hybrid capacitor constructed with the composite anode displays high power/energy densities and long lifespan. Abstract: It is urgent for sodium-ion hybrid capacitors (SIHCs) to exploit a porous carbon anode that integrates high reversible specific capacity, rapid kinetics and superb cyclability. Herein, a three-dimensional dumpling-like glyururil-derived porous carbon@RGO composite (GLCG) constructed from nitrogen-doped (10.29 at.%) hierarchical porous carbon filling and highly conductive flexible RGO wrapper is synthesized. As for the Na half-cell, GLCG anode delivers high reversible specific capacity (282 mAhg -1 at 0.05 A g −1 ) as well as superb rate capability (122.8 mAhg -1 at 10 A g −1 ) and lifespan (3000 cycles at 2 A g −1 ). Moreover, the origin of the excellent sodium-ion storage properties of GLCG is revealed by in-depth mechanism analysis. Consequently, a SIHCs with GLCG anode is constructed, which displays high energy density of 108 Wh kg −1, high power density of 14.2 kW kg −1 and long lifespan of 66% capacity retention after 5000 cycles at 2 A g −1 . This work provides an alternative avenue for the exploitation of high-performance carbon-based SIHCs anode. Graphical abstract: Image, graphical abstract